Pengaruh Good Governance Terhadap Prestasi Kerja Pegawai Di Kantor Kecamatan Majauleng Kabupaten Wajo - Erna, Erna; Iwan Mamminanga; Andi Renilda Filyandini (Journal of Research and Development on Public Policy, 2023)
Good governance is always related to a job, especially good quality work. Government organizations are expected to be able to provide quality work and good quality, so that there is good work performance. The type of research used is census research where research takes all members of the population as respondents (data source) and uses a questionnaire as the main data collection tool. By using a quantitative approach and using descriptive methods to determine the effect of good governance on employee performance at the Majuleng District Office, Wajo Regency. The results of the analysis of research data on Good Governance and Work Performance, that Good Governance at the Majauleng District Office is in the good category. Likewise with the Job Performance variable which is in the good category. The influence of the good governance variable on work performance is in the very strong and positive category with significant data. It can be concluded from the results of the study entitled the influence of Good Governance on work performance as follows: Good Governance at the Majuleng District Office, Wajo Regency, is in the good category. The work performance of the employees of the Majauleng District Office, Wajo Regency, is in the very good category. The results of the data analysis show that the influence given is a very strong influence with a positive and significant relationship